PENGARUH HARGA, PROMOSI, KERAGAMAN PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI IRIAN SUPERMARKET & DEPT STORE AKSARA KOTA MEDAN - Ningsih Damanik, Surya; Sugianto, Sugianto; Atika, Atika (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
The aspects of the problem studied by the author are regarding the influence of price, promotion, product diversity and service quality on purchasing decisions at the Irian Supermarket & Aksara Dept Store in Medan City. The purpose of this research was to determine the influence of price, promotion, product diversity and service quality on purchasing decisions at Irian Supermarket & Aksara Dept Store, Medan City. The analysis technique used is quantitative methods. Data collection was carried out by distributing questionnaires and the questionnaire results were received back for processing. Data were analyzed using SPSS 25. Research results. Based on the results of the t test, it can be seen that price has a significant effect on consumer purchasing decisions at Irian Supermarket & Literacy Dept. Strore Medan City, Promotion has a significant effect on consumer purchasing decisions at Irian Supermarket & Literary Strore Dept. Medan City, Product diversity has a significant influence on consumer purchasing decisions at Irian Supermarket & Dept. Strore Aksara, Medan City, and service quality has a significant influence on consumer purchasing decisions at Irian Supermarket & Dept. Strore Aksara, Medan City. As well as the results of the F test, it can be seen that price, promotion, product diversity and service quality has a significant effect simultaneously (together) on consumer purchasing decisions at Irian Supermarket & Literacy Strore Dept. Medan City with a coefficient of determination of 63.8%. Based on the results of statistical testing, it can be seen that simultaneously (together) the variables price, promotion, product diversity and service quality have a significant effect on the dependent variable of purchasing decisions at Irian Supermarket & Dept Store Aksara, Medan City.